COMMUNICATION STRATEGY USED BY LOCAL GUIDE IN MUSEUM KESEJARAHAN JAKARTA - Suwantica Kusumandari; Ferdias Prihatna Sari (Jurnal Akrab Juara, 2021)
The objective of this paper focused to describe communication strategy used by local guide in museum kesejarahan jakarta, especially types of strategy in communication and the function of each strategy for the local guide to solving their problem on the museum. Communication strategy is the important things that the guide needed to build good conversation with the foreigners visitor there. The objective of this study are to find out the most dominant type of types of strategy in communication and the functions of each strategy when the guide faced the problem when guiding, the writer used descriptive qualitative method. The data is in the conversation. The data collection was done by collecting the data from observation and the conversation problem with each foreigners tourist. The writer analyzes some conversation that can be shown as the problem faced by the tour guide and it used theory by Marianne Celce Murcia in journal of Ekayati and Saniaty. It can be classified into 5 types of communication strategy. The dominant of those theory were interaction strategy.